The Effect Of Concentration Ratio Of Sugarcane Bagasse And Starch Fiber On The Characteristics Of Natural Styrofoam For Environmentally Friendly Food Packaging Raw Materials - Reza Fauzan; H Harunsyah; M Yunus; Halim Zaini; S Syafruddin (Jurnal Sains dan Teknologi Reaksi, 2023)
Styrofoam is one type of food packaging that we often find. Styrofoam has excellent heat and cold resistance so it is used as an insulator. The ability to withstand good temperatures, lightweight and practical encourages the use of styrofoam as a food and beverage packaging material. However, Styrofoam contains many harmful substances and is not environmentally friendly. One solution is to replace the material for making styrofoam which is environmentally friendly called biodegradable foam. Sugarcane bagasse fiber has the potential as a basic material for making biodegradable foam. The purpose of this experiment is to determine the effect of the addition of bagasse fiber on the characteristics of biodegradable foam. This experiment uses a complete randomized design method with sugarcane bagasse fiber concentration treatment. The characteristic tests carried out include tensile strength test, water absorption test, biodegradation test, and thermogravimetric analysis. From the results of bagasse fiber decomposed 9,130 mg and still remaining 1,13 mg. The optimum concentration of biodegradable foam bagasse fiber on water absorption, biodegradation rate, and tensile strength in the 90:10 composition sample. The results of functional group analysis showed O-H and C-O groups which indicated that biodegradable foam is easily degraded by microorganisms in the soil.Â Keywords: Biodegradable foam, bagasse, cassava starch, packaging.Â